2019
DOI: 10.1155/2019/6279164
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Analysis of Unsteady Temperature in Thermal Insulation Supporting Roadway

Abstract: High geothermal hazard is a basic problem that must be solved in deep mining; thereby the research on thermal insulation supporting for high temperature control of deep roadway is increasing. However, the quantitative analysis of its thermal insulation effect is yet to be carried out. By building the physical model and control equations of the thermal insulation supporting roadway and considering heat-humidity transfer at wall, the temperature field distribution of surrounding rock and airflow is numerically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous studies gener ally treated the surrounding rock as zero thickness and set the rock wall temperature as constant, using either temperature-boundary conditions or convective-heat-transfer-coef ficient-boundary conditions [21,36]. However, as the ventilation time increased, hea transfer within the rock and convective heat transfer between the rock wall and the air flow were coupled [37]. Considering the interaction of heat transfer in solids and convec tion in fluids, solid structures were added to the model to significantly improve the accu racy of the simulation.…”
Section: Geometric Modeling and Meshingmentioning
confidence: 99%
“…Previous studies gener ally treated the surrounding rock as zero thickness and set the rock wall temperature as constant, using either temperature-boundary conditions or convective-heat-transfer-coef ficient-boundary conditions [21,36]. However, as the ventilation time increased, hea transfer within the rock and convective heat transfer between the rock wall and the air flow were coupled [37]. Considering the interaction of heat transfer in solids and convec tion in fluids, solid structures were added to the model to significantly improve the accu racy of the simulation.…”
Section: Geometric Modeling and Meshingmentioning
confidence: 99%
“…However, each of these equations is typically a multivariate function, so when the application scope is beyond the statistical scope, the error will be relatively large. In recent years, the numerical calculation models (e.g., FEM and FVM) for a single line of surrounding rock-airflow heat transfer have been included in the scholars' discussion scope [21][22][23]; nevertheless, since the relationships between the air temperature and numerous influencing factors (e.g., wall roughness, thermal physical parameters of rock, and moisture content of airflow) are highly nonlinear, scholars find it extremely hard to figure out parameters in these models. In addition, the models are rarely applied to whole ventilation networks on engineering sites as a result of missing parameters, deficient validation, and insufficient an description of the heat and mass transfer mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the insulation layer greatly reduced the rock wall temperature and the disturbance range of the surrounding rock temperature; The smaller the thermal conductivity of the thermal insulation layer, the greater the decrease in roadway wall temperature and the greater the rate of change of its decrease curve. Zhang et al [20] used numerical simulation method to simulate and analyze the temperature field of the thermal insulation supporting roadway. The results showed that the temperature field of the heat insulation support structure does change significantly, but it has the effect of weakening the convective heat transfer between the surrounding rock wall and the airflow.…”
Section: Introductionmentioning
confidence: 99%